ANALISIS ARTIKEL TERKAIT EFISIENSI SUMBER DAYA MANUSIA DI SEKTOR TRANSPORTASI INDONESIA - Muhammad Zidan; Lewi Barkah; Prince Eduardo Haloho; Siti Sahara (Cross-border, 2023)
This study aims to determine the efficiency of human resources in the transportation sector in Indonesia. The type of research used in this research is descriptive qualitative research. The results of the study show that good human resource efficiency can improve quality in the transportation sector through three main aspects, namely the recruitment and selection of the right workforce, continuous employee training and development, and adequate employee appreciation and motivation. This research implies that good human resource efficiency can improve quality in the transportation sector in Indonesia.